Finite element method‐based modelling of flow rate and temperature distribution in an oil‐filled disc‐type winding transformer using COMSOL multiphysics. Issue 4 (1st April 2017) - Das, Anu Kumar; Chatterjee, Saibal
Abstract : Thermal design of oil filled distribution and power transformers is essential for obtaining the location of 'hot‐spot' of the transformers. This study presents the analysis of 2D and 3D model for the simplified section of an oil‐filled disc‐type winding power transformer. Both models developed using COMSOL Multiphysics 5.1 were validated with the experimental and numerical results available in literatures. The analysis of the flow rate and the temperature distribution accurately reveals the location and the temperature of the 'hot‐spot'. Further, the parametric study using the 3D model shows that the combined effect of variation in the vertical cooling duct width and the local cross‐section area in the horizontal cooling duct has a significant influence on the location of the 'hot‐spot' and a minor influence on its temperature (i.e. ±3%). The analysis results in this study shall be beneficial from the point of view of design development in transformers.